Transcriptomic analysis reveals protein homeostasis breakdown in the coral Acropora millepora during hypo-saline stress - Catalina Aguilar; Jean-Baptiste Raina; Sylvain Fôret; David C. Hayward; Bruno Lapeyre; David G. Bourne; David J. Miller (BMC Genomics, 2019)
Abstract Background Coral reefs can experience salinity fluctuations due to rainfall and runoff; these events can have major impacts on the corals and lead to bleaching and mortality. On the Great Barrier Reef (GBR), low salinity events, which occur during summer seasons and can involve salinity dropping ~ 10 PSU correlate with declines in coral cover, and these events are predicted to increase in frequency and severity under future climate change scenarios. In other marine invertebrates, exposure to low salinity causes increased expression of genes involved in proteolysis, responses to oxidative stress, and membrane transport, but the effects that changes in salinity have on corals have so far received only limited attention. To better understand the coral response to hypo-osmotic stress, here we investigated the transcriptomic response of the coral Acropora millepora in both adult and juvenile life stages to acute (1 h) and more prolonged (24 h) exposure to low salinity. Results Differential gene expression analysis revealed the involvement of both common and specific response mechanisms in Acropora. The general response to environmental stressors included up-regulation of genes involved in the mitigation of macromolecular and oxidative damage, while up-regulation of genes involved in amino acid metabolism and transport represent specific responses to salinity stress. Conclusions This study is the first comprehensive transcriptomic analysis of the coral response to low salinity stress and provides important insights into the likely consequences of heavy rainfall and runoff events on coral reefs.